2015
DOI: 10.1371/journal.pone.0120137
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Modulates Mesenchymal Stromal Cell Proliferation and Gene Expression

Abstract: Statins are widely used hypocholesterolemic drugs that block the mevalonate pathway, responsible for the biosysnthesis of cholesterol. However, statins also have pleiotropic effects that interfere with several signaling pathways. Mesenchymal stromal cells (MSC) are a heterogeneous mixture of cells that can be isolated from a variety of tissues and are identified by the expression of a panel of surface markers and by their ability to differentiate in vitro into osteocytes, adipocytes and chondrocytes. MSC were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
(48 reference statements)
0
14
1
1
Order By: Relevance
“…29 Statins are a group of widely used lipid lowering drugs that block the biosynthesis of cholesterol. 30 Simvastatin(SIM) increased the proliferation of smaller MSCs, 30 and can increase osteogenesis of them. 31 The mechanism for enhancing osteogenesis is mediated by increasing both actin filament organization and cell rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…29 Statins are a group of widely used lipid lowering drugs that block the biosynthesis of cholesterol. 30 Simvastatin(SIM) increased the proliferation of smaller MSCs, 30 and can increase osteogenesis of them. 31 The mechanism for enhancing osteogenesis is mediated by increasing both actin filament organization and cell rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…8 Simvastatin induces increased pluripotency and protects against cellular senescence in MSCs. 6 It also improves the migration of bone marrow-derived MSCs via the PI3K/AKT pathway, 14 and enhances the neurogenesis of cultured neural stem cells and elevates Notch-1 protein expression. 7 Simvastatin exhibits increased dentin sialoprotein and calcium deposition, and it has been suggested that it can promote odontoblastic differentiation in dental pulp stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 The effects of simvastatin on mesenchymal stem cells (MSCs) have been observed in previous studies. [6][7][8][9] Simvastatin has been reported to increase the therapeutic effects of nucleus pulposus stem cells by increasing the number of those cells. 8 It has also been shown to induce enhanced proliferation of cultured neural stem cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased numbers of bone marrow mesenchymal stem cells (BMSCs) and unbalanced differentiation of osteoblasts and adipocytes are vital mechanisms underlying osteoporosis . Recent studies showed that simvastatin could promote bone formation and osteogenic differentiation of BMSCs, although the mechanism by which this occurs remains unknown. Signaling pathways capable of modulating osteogenic differentiation of BMSCs are considered potential targets of simvastatin activity .…”
Section: Introductionmentioning
confidence: 99%